Efektivitas Pelayanan Surat Keterangan Catatan Kepolisian (SKCK) Online Sebagai Persyaratan Dokumen Administrasi di Polresta Kupang Kota - Eil Grace Sinlaeloe; Melkisedek Noh Bernabas Cervesius Neolaka; Rouwland Alberto Benyamin; Made Ngurah Demi Andayana (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
Digital transformation in public services has encouraged government institutions to develop technology-based services, including the Online Police Record Certificate (SKCK) service at Kupang City Regional Police Resort. This study aims to analyze the effectiveness of the Online SKCK service as an administrative requirement at the Kupang City Regional Police Resort. The research employed a qualitative approach with a descriptive method. Data were collected through observation, interviews, and document analysis involving service officers and users of the Online SKCK service. Data were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings indicate that the Online SKCK service has improved accessibility, service efficiency, and transparency through the implementation of the PRESISI POLRI application. Based on the effectiveness indicators, namely program understanding, target accuracy, timeliness, goal achievement, and real change, the service can be categorized as moderately effective. Target accuracy and real change emerged as the strongest indicators, while program understanding and timeliness still face several challenges, including limited digital literacy among users, application system disruptions, and data verification issues. Nevertheless, the Online SKCK service has provided significant benefits in supporting the modernization of public services. The study concludes that improving system quality, strengthening public outreach, and developing a more integrated service system are necessary to optimize the effectiveness of the Online SKCK service at the Kupang City Regional Police Resort.